Oppotunities for biotechnology in cowpea - Monti, L.; Murdock, L.; Thottappilly, G. (1997)
Several applications of biotechnology have been successfully used recently in cowpea. A molecular map of cowpea has been constructed using RFLP markers, and this has already facilitated the localization of certain quantitative trait loci; gene chromosome localization using in situ hybridization is in progress. Appropriate bioassays have been developed that have facilitated the identification of candidate genes for insect pest resistance in cowpea, including Bacillus rhttrins>ensis protoxin genes, and genes coding a-amylase inhibitor, protease inhibitor, and lectins. Since cowpeas are "recalcitrant" to regenerate "in vitro", several attempts have been made to develop a reliable protocol for differentiating shoots from calli obtained through in vitro tissue cultures. Thus far, only regeneration from already meristem-rich tissues has been obtained. The best results were obtained using the herbicide, thidiazuron. As a growth regulator to induce multiple bud proliferation. Agrobdctcriiuu-medrdled plant genetic transformation remains an approach that requires considerable further work to be efficient. Direct plasmid DNA transfer into meristemalic cells has also been attempted using micro projectile bombardment; rates of genetic transformation are too low to be useful. Recently, two new transformation methods were set up on in vivo plants: the first is based on electro injection of plasmid DNA directly into meristemalic cells, and the second involves the inoculation of buds with Agrobacterium; these two methods do not need in vitro regeneration and are giving promising results.